Pengembangan Flipbook Bersuara “Mubina” pada Pembelajaran Pendidikan Agama Islam di SDN Ciuyah II Kelas 4 - Maharani, Aura Setya; Salsabilla, Dita; Mu`adah, Nurroh Muna; Aeni, Ani Nur (ALSYS, 2025)
This study aims to develop and evaluate the “MUBINA” Voiced Digital Flipbook as an innovative learning media in Islamic Religious Education (PAI) subjects for grade IV elementary school students. This research was conducted to answer the need for more interactive and interesting learning media to increase students' understanding of Islamic history, especially regarding the role of the Prophet Muhammad SAW in building the City of Medina. The research method used is design and development (D&D) with a qualitative approach. Data were collected through observations, interviews, and questionnaires involving fourth grade students of SDN Ciuyah II, PAI teachers, and material experts. The instruments used include digital applications such as Canva, CapCut, and Heyzine in making and testing interactive flipbooks. The results showed that the use of the “MUBINA” Digital Voiced Flipbook significantly increased students' learning motivation, facilitated understanding of the material, and made the learning process more interesting than conventional methods. Learners showed a higher interest in Islamic history material and more easily remembered key concepts such as the construction of the Prophet's Mosque and the Madinah Charter. We hope that the “MUBINA” Digital Voice Flipbook can be an effective alternative learning media in Islamic education at the elementary school level. The use of technology in learning should continue to be developed to improve the overall quality of education.